Luther, Lutherans, and Jews: Looking to the Second Five Hundred Years - Pettit, Peter A. (Studies in Christian-Jewish Relations, 2018)
The 500th anniversary of Martin Luther's birth, in 1983, prompted extensive historical and theological research regarding Luther's vitriolic pronouncements about Jews and Judaism. This, in turn, led many Lutheran church bodies to repudiate Luther's anti-Jewish invective. At the 500th anniversary of The 95 Theses, what tasks remain for Lutherans in dealing with the Reformer's legacy and fashioning a positive relationship with the Jewish people? The suggested tasks are a systematic re-formulation of Christian theology, recognizing the place of the land in the biblical promise to Israel, and reconciling with the Jewish people as a normal part of society. The last constitutes a "new Jewish question," this one put to Christians rather than Jews.